Naming the Days: The Influence of Ancient Astronomy on Modern Religious and Cultural Practices - Belay Sitotaw Goshu; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2024)
A rich interplay of astronomy, religion, and mythology is reflected in the naming of days across cultures, providing insights into how societies organized time and perceived the universe. This study focuses on Ethiopia's distinctive calendar and religious influence while examining the cultural importance of weekday naming customs in other countries. The goal is to scrutinize how astronomical observations and antiquated customs from Mesopotamia, Egypt, Asia, and Ethiopia combine to influence modern timekeeping. This study tracks the development of day-naming customs throughout multiple civilizations by analyzing historical documents, linguistic trends, and religious writings using a comparative cultural analysis approach. The findings demonstrate that while many cultures, including Ethiopians, name their days after solar or lunar events, religious beliefs also play a major role, particularly in Ethiopian Orthodox Christian traditions. Day naming is a valuable tool for tracking time and a representation of cultural identity, according to the study, which finds that day name is heavily influenced by mythology and religion. It is suggested that conventional timekeeping methods be preserved via digital preservation and teaching and that interdisciplinary study be encouraged to delve deeper into these relationships.